2022
DOI: 10.1093/ofid/ofac121
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV Virologic Failure and Switch to Second-Line Therapy: A Systematic Review and Meta-analysis of Data From Sub-Saharan Africa

Abstract: Introduction The late recognition of virologic failure (VF) places persons with HIV in sub-Saharan Africa at risk for HIV transmission, disease progression and death. We conducted a systematic review and meta-analysis to determine if the recognition and response to VF in the region has improved. Methods We searched for studies reporting CD4 count at confirmed VF or at switch to second-line ART. Using a random-effects meta-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Even PWH with advanced disease may feel a return to health as soon as 6 to 12 months after starting ART. VL is an important clinical indicator of ART adherence ART response, our study findings enforce that the early detection of virological failure and achievement of virological suppression are critical to improving HRQoL in this population [ 31 ]. Furthermore, significant positive associations between CD4 and utility support the importance of CD4 count monitoring in clinical settings in Uganda.…”
Section: Discussionsupporting
confidence: 56%
“…Even PWH with advanced disease may feel a return to health as soon as 6 to 12 months after starting ART. VL is an important clinical indicator of ART adherence ART response, our study findings enforce that the early detection of virological failure and achievement of virological suppression are critical to improving HRQoL in this population [ 31 ]. Furthermore, significant positive associations between CD4 and utility support the importance of CD4 count monitoring in clinical settings in Uganda.…”
Section: Discussionsupporting
confidence: 56%
“…A systematic review and meta-analysis from sub-Saharan Africa reported a mean delay between confirmation of treatment failure and switch of therapy of 530 days. [ 25 ] In Kenya, a review of program data reported the average time taken to ART regimen switch in clients with treatment failure is 411 days.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adherence challenges, the high cost or unavailability of second‐line regimens may be the reasons for delayed switching in low/upper middle‐income countries [ 8 , 26 , 27 ]. The lack of routine VL testing has also contributed to delayed VF detection and first‐line ART switches [ 28 ]. Switching to DTG as per WHO recommendation has been implemented across several countries.…”
Section: Discussionmentioning
confidence: 99%